Reorientasi BPR Dari Perusda Menjadi Perseroda: Indonesia - Adji Suradji Muhammad (Prodi Ilmu Administrasi Negara, 2018)
Rural Banks are financial institutions formed by the regional government in an effort to provide services in the financial sector. Besides providing financial services, BPRs are also an effort for local governments to bring in local revenues. So far, BPRs have limited capital because capital is only sourced from the APBD. With the Minister of Home Affairs Regulation No. 94 of 2017 concerning Management of Rural Banks Owned by Local Governments. With the presence of the Minister of Home Affairs, the regional government can change the form of BPR from the regulation to the company. With this change in form, professionalism and capacity building. Data and Data Sources Associated with data and data sources in this study the normative legal research uses secondary data while for empirical legal research using primary data Data processing and data analysis used are using qualitative methods. The asset value of a company describes the size of the company. Value of assets also illustrates the fundamental potential of a company. Thus if we want to see the growth potential of a company is to look at its asset growth. While the company's profits show the company's advantages and opportunities to continue to grow. Therefore, these two variables become a significant variable in analyzing a company's growth. Increasing service in the financial sector which tends to increase can not be fulfilled optimally by BPR Bestari due to limited capital. To improve the financial capability of BPR Bestari, it is necessary to increase capital